Embedding Community-Based Circular Economy Initiatives in a Polycentric Waste Governance System: A Case Study - Istiyani, Ambar; Handayani, Widhi (The Indonesian Journal of Planning and Development, 2022)
This research explores the approach of embedding community-based initiatives in practicing circular economy based on a case study of waste bank movement in Salatiga, Central Java, and explains how the waste banks interact with multi sectors and levels. Data is gathered from documentary studies, in-depth interviews, and observations; and analyzed with a polycentric governance approach, which sheds light on cross-organizational collaborative arrangements. The study results show that the community-based circular economy initiatives through waste banks in Salatiga result from either a top-down approach that the municipal government instructs or a bottom-up approach that Civil Society Organizations (CSOs) and communities initiate. Thus it is significant to note that CSOs play essential roles in waste management, and it completes the model proposed by the previous study. The study findings also show that embedding community-based waste management through waste banks in Salatiga can enhance broader circular economy practices, strengthen the linkages across sectors and levels, and balance the authorities in a polycentric waste governance system. Therefore, waste banks must be recognized as reliable institutions governing waste, especially in urban areas.